Navigating the New Normal: Performance of Stock Market During Pandemic - Dipendra Karki (Pravaha, 2022)
This study analyzes the effect of COVID-19 on the Nepalese stock market. It utilizes data from January 23, 2020, to December 31, 2020, and examines variables such as confirmed cases, deaths, lockdowns, and interest rates. The results reveal a significant negative impact of COVID-19 related variables, interest rates, and lockdowns on the stock market performance, while total deaths had a positive impact. The study also found that all variables studied had a significant influence on the performance of all sectors. These insights are important for investors, market players, businesses, policymakers, and governments to establish recovery action plans and help investors to make better investment decisions.